Understanding Pediatric Patient's Perspective on Neurostimulation (Cefaly®™) for Migraine Treatment: A Focus Group Discussion - Julia Anne Craig; Kelsey Wright; Pilar McCann; Taylor Ness; Thilinie Rajapakse (Spectrum)
Purpose: Migraines are highly prevalent among children and adolescents, leading to significant disability. External trigeminal nerve stimulation (Cefaly®) is an emerging alternative treatment for migraine. These non-invasive wearable devices deliver electrical impulses through the skin to reduce pain transmission. Cefaly® has been government-approved for use in adults but has not been formally studied in pediatric-aged populations. We conducted a focus group with pediatric patients (aged 16-17) and a patient partner (aged 18) diagnosed with chronic migraine to investigate adolescent perspectives on the Cefaly® device. Involving adolescents ahead of a clinical trial is critical for understanding whether the Cefaly® device can be integrated into patients' lives and have a meaningful impact in real-world contexts for pain management.